Reactive oxygen species in the signaling and adaptation of multicellular microbial communities - Cáp, Michal; Váchová, Libuše; Palková, Zdena (Oxidative medicine and cellular longevity, 2012)
One of the universal traits of microorganisms is their ability to form multicellular structures, the cells of which differentiate and communicate via various signaling molecules. Reactive oxygen species (ROS), and hydrogen peroxide in particular, have recently become well-established signaling molecules in higher eukaryotes, but still little is known about the regulatory functions of ROS in microbial structures. Here we summarize current knowledge on the possible roles of ROS during the development of colonies and biofilms, representatives of microbial multicellularity. In Saccharomyces cerevisiae colonies, ROS are predicted to participate in regulatory events involved in the induction of ammonia signaling and later on in programmed cell death in the colony center. While the latter process seems to be induced by the total ROS, the former event is likely to be regulated by ROS-homeostasis, possibly H(2)O(2)-homeostasis between the cytosol and mitochondria. In Candida albicans biofilms, the predicted signaling role of ROS is linked with quorum sensing molecule farnesol that significantly affects biofilm formation. In bacterial biofilms, ROS induce genetic variability, promote cell death in specific biofilm regions, and possibly regulate biofilm development. Thus, the number of examples suggesting ROS as signaling molecules and effectors in the development of microbial multicellularity is rapidly increasing.
Keywords: houby; Reactive Oxygen Species; signální transdukce; Signal Transduction; Microbial Consortia; fyziologická adaptace; mikrobiální společenstva; Bacteria; Fungi; reaktivní formy kyslíku; Adaptation, Physiological